Biology of peripheral T cell lymphomas – Not otherwise specified: Is something finally happening?. Issue 1 (February 2016) - Maura, Francesco; Dodero, Anna; Carniti, Cristiana; Bolli, Niccolò
Abstract: Introduction: Peripheral T-cell lymphomas represent a rare, heterogeneous group of nodal and extra-nodal mature T-cell lymphomas. Among those, the subtype of PTCL not otherwise specified (PTCL-NOS) account for about 25% of all PTCL. While other PTCL subtypes are increasingly recognized as discrete entities based on specific genotypic and phenotypic alterations, the diagnosis of PTCL-NOS is currently performed on an "exclusion criteria" model, since PTCL-NOS lack pathognomonic features. Methods: In this review, we describe the classical pathological features of PTCL-NOS and integrate them with the most recent molecular findings. Results: Thanks to gene expression profiling and next generation sequencing approaches, we have recently improved our knowledge of PTCL in general and PTCL-NOS in particular. Indeed, specific patterns of gene expression were reported to segregate PTCL into more homogeneous subtypes associated with distinct clinical outcome. Furthermore, we describe how immunophenotypic, expression and mutational data helped to better define a new subgroup of PTCL-NOS displaying a global profile close to T Follicular Helper cell elements. Finally, we review how these new acquisitions are changing the current diagnostic approach to PTCL-NOS, and how phenotypic features and oncogenic pathways operative in these lymphomas are becoming targets of novel treatments. Conclusion: Although no recurrent and specific biological aberrations have been discovered yet, novel integrated genomic and transcriptomics approaches are significantly improving our knowledge of PTCL biology and support the development of new powerful diagnostic and prognostic markers, as well as targets of future therapies.